THE EFFECT OF SPIRITUAL THREATS ON THE DEVELOPMENT OF OUR SOCIETY - Yuldasheva M.M. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article highlights the role and place of media in learning and education of youth.